2019
DOI: 10.1093/jpe/rtz058
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection on flower size in invasive Cytisus scoparius along an elevation gradient

Abstract: Aims Established invasive plant species have more diverse gene pools than single populations in their home range. This genetic and often phenotypic variation allows for natural selection to act and produce rapid adaptations as an invasive species interacts with other members of the community. For an invasive flowering plant, interactions with pollinators may lead to adaptations to a heterogeneous pollinator community. The variation in the pollinator community in the invaded range is similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The local flower size adaptations of plants to elevational gradient may be affected by biotic factors, such as pollinator community (Kuriya et al, 2015) or simply by the abiotic selective pressure, regardless of changes in the pollinator community (Bode and Dufresne, 2020). Previous research has shown that some plant species tend to develop larger flowers at a higher altitude (Malo and Baonza, 2002;He et al, 2017;Bode and Dufresne, 2020), while some studies have shown that there is no common regularity in the correlation between floral size and altitude itself (Nagano et al, 2014). When both floral display size and flower color vary within a plant species, each has the potential to play an important role in pollinator attraction and subsequent seed set (Malerba and Nattero, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The local flower size adaptations of plants to elevational gradient may be affected by biotic factors, such as pollinator community (Kuriya et al, 2015) or simply by the abiotic selective pressure, regardless of changes in the pollinator community (Bode and Dufresne, 2020). Previous research has shown that some plant species tend to develop larger flowers at a higher altitude (Malo and Baonza, 2002;He et al, 2017;Bode and Dufresne, 2020), while some studies have shown that there is no common regularity in the correlation between floral size and altitude itself (Nagano et al, 2014). When both floral display size and flower color vary within a plant species, each has the potential to play an important role in pollinator attraction and subsequent seed set (Malerba and Nattero, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Trait variation among populations has been associated with changes in natural selection pressure along elevation ( Bode and Dufresne 2019 ). Long-term adaptation to environmental factors would thus result in genetically based changes in phenotypic traits ( Marin et al 2019 ; Pimpinelli et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%